Investing in Schooling In Chile: The Role of Information about Financial Aid for Higher Education - Dinkelman, Taryn; Martínez A., Claudia (The Review of Economics and Statistics, 2014)
We investigate the impacts of providing low-income Chilean adolescents with information about how to finance higher education and ask whether providing parents with the same information magnifies the effects on schooling outcomes. We randomly assigned eighth graders and some parents to receive information about aid for higher education. Exposure to information raised college preparatory high school enrollment, primary school attendance, and financial aid knowledge, with gains concentrated among medium- and high-grade students. Parental exposure to information did not significantly magnify these effects. Our results demonstrate that access to relevant information about financial aid affects important schooling choices long before tertiary education begins.